Tingkat Kebahagiaan Masyarakat setelah Adanya Mural di Kelurahan Sukawarna Kecamatan Sukajadi Bandung - Ariesa Pandanwangi; Ida Ida; Ratnadewi Ratnadewi; Rosida Tiurma Manurung; Iman Budiman; Vincent Vincent (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Abstrak Tujuan penelitian ini yaitu untuk mengukur tingkat kebahagiaan masyarakat Kelurahan Sukawarna setelah dibuatnya mural di lingkungan mereka. Metode yang digunakan adalah metode campuran (mix method). Pertama metode penelitian berbasis komunitas dan kedua menggunakan survei. Hasil penelitian ini menunjukkan pertama, masyarakat berhasil membuat karya mural dengan tema kearifan lokal berupa benda-benda hunian, flora, dan fauna yang diwarnai. Secara estetika, visualisasi dinding menjadi menarik, sehingga lingkungan menjadi menarik dan orang dapat mengambil foto diri di sana. Kedua, berdasarkan survei dengan adanya mural mempengaruhi tingkat kebahagiaan masyarakat sebesar 49,9 % Abstract Environmental problems, one of which is the space for the actuality of citizens. The mural is one of the attractive locations for environmental attraction and can be a marker of an urban area. At present RW 04 Sukawarna Urban Village has not been well organized, so it requires a colorful environment that can be one of the interesting areas in Bandung. This service is guided by the facilitator with the principle of partnership assistance with the Asset Based Community. Development method. The community service servants will complete a 12 meter long wall with a height of 3 m. The wall will be painted on and given color. The result of this service is a mural work with the theme of local wisdom in the form of objects of residential objects, flora and fauna that are colored. Aesthetically, the visualization of the walls becomes interesting, so the environment becomes interesting, and people can take self-photographs there. Economically, the environment can be an attraction and an incentive for tourists who come gradually, so that the community can empower economic growth in the future.